2012
DOI: 10.1021/ie301706s
|View full text |Cite
|
Sign up to set email alerts
|

Acidic and Catalytic Properties of Modified Clay for Removing Trace Olefin from Aromatics and Its Industrial Test

Abstract: The commercial clay modified with zeolite and La 2 O 3 was characterized by thermoprogrammed desorption (t.p.d.) of NH 3 and pyridine adsorption followed by Fourier transform infrared spectroscopy (FTIR). The result showed that the weak Lewis acid plays an important role in the alkylation reaction between olefin and aromatics which obeyed the carbonium ion mechanism. The industrial test was conducted in the 450kt/a industrial PX device at Sinopec Zhenhai Company for removing trace olefins from aromatics. It ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 20 publications
0
27
0
Order By: Relevance
“…In order to protect the adsorbent, the bromine index which is an indicator of the presence of olefinic bonds is required to be less than 20 mg Br/100 g. Therefore, these contaminants must be removed before aromatic streams are sent to the petrochemical processes. It has been approved that these harmful impurities can be removed by acid-catalyzed alkylation of the appropriate aromatics [3][4]. In commercial plants, the purification process uses the clay treating [5] or the modified clay treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In order to protect the adsorbent, the bromine index which is an indicator of the presence of olefinic bonds is required to be less than 20 mg Br/100 g. Therefore, these contaminants must be removed before aromatic streams are sent to the petrochemical processes. It has been approved that these harmful impurities can be removed by acid-catalyzed alkylation of the appropriate aromatics [3][4]. In commercial plants, the purification process uses the clay treating [5] or the modified clay treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In the spectra, vibration bands were observed in the wavenumber range of 1400–1600 cm –1 , which were attributed to the interaction of pyridine with Lewis (L) and Brønsted (B) acid sites on the sample surface. 8 , 13 The band at around 1450 cm –1 was attributed to pyridine adsorbed on the L acid sites. Another band at around 1490 cm –1 was ascribed to the contributions of both the L and B acid sites.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, two intense signals at ñ = 1454 and 1625 cm À1 attributed to pyridine vibrations confirm the presenceo fL ewis acid sites (L). [41,42] The B/L ratio evaluated from the integration area of the signals at ñ = 1454 and 1540 cm À1 ( Figure S4) indicated that as the silica coating increasedt he amount of Bs ites increased and that of Ls ites decreased.…”
Section: Resultsmentioning
confidence: 99%